Estrategias de comunicación de la Casa de la Cultura, Núcleo Los Ríos, para impulsar la cultura en la Provincia - Carrillo Guerrero, Elvira Mariana (2023)
In this research on the Communication Strategies of the House of Culture, Núcleo Los Ríos, to Promote Culture in the Province, the objective of the study is to analyze the level of reach and identify the communication strategies to propose news strategies to the House of Culture, Núcleo Los Ríos, with a sequential mixed method with qualitative and quantitative phases in which the analysis and interpretation of the findings obtained in this research are deepened through the surveys and interviews carried out. In addition, with mixed research, an understanding of the topic is achieved about the communication strategies used by the House of Culture, Núcleo Los Ríos, obtaining favorable results for the institutionality, recommending workshops, events, cultural acts of different categories, dances, theater , among others. In conclusion, it is determined that the use of communication strategies are an important part for the adequate dissemination and promotion of the cultural heritage of the House of Culture, Núcleo de Los Ríos.